ANALISIS PENDAPATAN MASYARAKAT PELADANG DI KAWASAN PERBATASAN KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Widyawati, Yuli; Roslinda, Emi (Universitas Tanjungpura, 2019)
Shifting cultivation is an activity that cannot be separated from the community around the border of Kapuas Hulu Regency. Various factors influence the income of farmers. The aims ofÂ this research was to determine the income of rice farming on farmers and the relationship between income and the land area, the number of family members working in the fields and the number of working hours. Data was collected for two months from March 2016 until May 2016 at the study site through interviews with 97 families who were deliberately selected based on certain criteria. The method used in this study is a survey method with interviews using questionnaires. The collected data analyzed using associative descriptive analysis and multiple linear regression analysis. The results showed that the average net income obtained by farmers is Rp. 2,379,917.76 / respondent / planting season. If the labor wage costs are calculated, the farmer's income becomes Rp. -4,181,680,186 / respondent / planting season due to pest attacks. The results of the regression analysis show the relationship between farmer income and the variable land area, the number of family members working in the field and the number of working hours simultaneously have a significant effect on farmer income. Partially, only the variable number of working hours has a significant effect on farmer income in the border area ofÂ Kapuas Hulu Regency.Keywords: income, land area, working hours, family members, cultivators